2021
DOI: 10.1039/d0ra05468b
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in Pt-based electrocatalysts for PEMFCs

Abstract: In this paper, the latest progress in the design of Pt-based ORR electrocatalysts is reviewed, including the understanding of research progress in the synthesis of high activity and high stability catalysts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(22 citation statements)
references
References 134 publications
0
18
0
Order By: Relevance
“…Furthermore, these catalysts must be able to operate for a long time in harsh PEMFC conditions. Currently, only Pt‐based catalysts satisfy both the efficiency and (to some extent) the durability requirements [12,13] . Very recent studies on metal and N‐codoped graphene/carbon nanostructures showed great promise that these materials can replace Pt in fuel cell ORR catalysis [10,14] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, these catalysts must be able to operate for a long time in harsh PEMFC conditions. Currently, only Pt‐based catalysts satisfy both the efficiency and (to some extent) the durability requirements [12,13] . Very recent studies on metal and N‐codoped graphene/carbon nanostructures showed great promise that these materials can replace Pt in fuel cell ORR catalysis [10,14] .…”
Section: Introductionmentioning
confidence: 99%
“…Currently, only Pt‐based catalysts satisfy both the efficiency and (to some extent) the durability requirements. [ 12 , 13 ] Very recent studies on metal and N‐codoped graphene/carbon nanostructures showed great promise that these materials can replace Pt in fuel cell ORR catalysis. [ 10 , 14 ] Various experimental and theoretical studies have been performed on PGM‐free nanostructure with Mn, Fe, Co, Ni, and Cu metal centers, and the observed activities have been found to be comparable to that obtained with the standard Pt catalyst.…”
Section: Introductionmentioning
confidence: 99%
“…Although Pt is an ideal material for electrocatalysis, its high cost and scarcity limit the commercial application of PEMFC [ 21 , 36 ]. In order to improve the stability and activity of ORR, the electronic structure of Pt needs to be adjusted to solve the key problems of the surface adsorption of various oxygen-containing intermediates in the ORR process.…”
Section: Controllable Preparation Of Pt-based Orr Catalystsmentioning
confidence: 99%
“…At present, Pt-based alloy catalysts have also been widely used in commercial applications. For example, Toyota Mirai has used a Pt 3 Co alloy catalyst for commercial PEMFC vehicles, and General Motors has also actively tested Pt 3 Ni alloy catalysts [ 36 ]. Compared with the current commercial platinum on carbon (Pt/C) catalyst, the catalytic performance and stability have been significantly improved.…”
Section: Introductionmentioning
confidence: 99%
“…Pt-based catalysts such as Pt–Co, Pt–Cu, Pt–Ni, etc. have been shown to exhibit higher oxygen reduction reaction (ORR) activity than platinum for PEMFC. Commercial Pt-based (PtCo) catalysts (nanoparticles 3–5 nm) supported on carbon black are considered the current standard catalysts offering high surface areas and high specific activity. Unfortunately, they are limited by corrosion of the C and Pt dissolution/agglomeration through the electrochemical Ostwald ripening mechanism, which is reflected by a fast and significant loss of electrochemical surface area (ECSA) over time during fuel cell operation. …”
Section: Introductionmentioning
confidence: 99%